Investigating the fate of copper in a laboratory‐based toxicity test with embryos of Mytilus galloprovincialis: Copper mass balance of a closed bioassay. (11th February 2019) - Zitoun, Rebecca; Hassler, Christel; Clearwater, Susan J.; Thompson, Karen J.; Albert, Anathea; Sander, Sylvia G.
Abstract: The production of accurate and reliable data on metal toxicity during ecotoxicological bioassays is important for credible environmental risk assessments and management in aquatic environments. Actual measurements and reporting of contaminant concentrations in bioassays are, however, often disregarded; and potential contaminant loss attributable to adsorption processes (e.g., wall adsorption) in bioassays is widely omitted, which can have detrimental effects on calculated metal toxicity thresholds. In the present we assessed copper (Cu) mass balance during a standard 48‐h bioassay test with blue mussel ( Mytilus galloprovincialis ) embryos to evaluate effects on calculated toxicity endpoints. We demonstrated that measured Cu concentrations at the test conclusion need to be used to quantify the risk of Cu toxicity because nominal Cu and initial Cu concentrations underestimate overall Cu toxicity by up to 1.5‐fold, owing to Cu loss in solution attributable to adsorption and bioaccumulation processes. For the first time we provide evidence that extracellular adsorption to the biological surface of the embryos is the most important sink for total dissolved Cu in a bioassay. We also established that adsorbed extracellular Cu accumulation reduces Cu toxicity to embryos, potentially by inhibiting Cu from entering the cell of the mussel embryo. Environmental factors (e.g., salinity and dissolved organic carbon) did not influence the partitioning of Cu within the laboratory‐based bioassay. The present results 1) demonstrate the importance of differentiating extra‐ and intracellular Cu pools to improve our understanding of Cu toxicity and associated processes, 2) reveal the potential for bias with respect to calculated Cu toxicity thresholds when results are based on nominal and initial Cu concentrations, and 3) point out the need to follow current guidelines for the testing of chemicals to standardize toxicity tests and data reporting. Environ Toxicol Chem 2019;38:561–574. © 2019 SETAC Abstract : Copper mass‐balance of a closed 48‐h bioassay with Mytilus galloprovincialis embryos.